Mechanism of Longevity Extension of Caenorhabditis elegans Induced by Schizophyllum commune Fermented Supernatant With Added Radix Puerariae - Deng, Yongfei; Liu, Han; Huang, Qian; Tu, Lingyun; Hu, Lu; Zheng, Bisheng; Sun, Huaiqing; Lu, Dengjun; Guo, Chaowan; Zhou, Lin (Frontiers in Nutrition, 2022)
Schizophyllum commune (S. commune) fermented supernatant with added Radix Puerariae (SC-RP) showed significant antioxidant activity in our previous work. However, the possible lifespan and healthspan extending the capacity of Caenorhabditis elegans (C. elegans) and the underlying mechanism were not illuminated. In this study, the effect of SC-RP on extending the lifespan and improving stress resistance of C. elegans were examined. Additionally, the underlying lifespan extending molecular mechanisms of SC-RP were explored. Treated with SC-RP at 10 μg/mL, the lifespan of C. elegans increased by 24.89% (P < 0.01). Also, SC-RP prolonged the healthspan of the nematode, including reducing lipofuscin levels, improving mobility and enhancing resistance to oxidative stress and heat shock. Moreover, superoxide dismutase and catalase activities were increased for SC-RP treated C. elegans. Meantime the intracellular levels of thiobarbituric acid reactive substances (TBARS) and reactive oxygen species (ROS) were attenuated. Express levels of eight genes including daf-2, daf-16, sod-3, skn-1, gst-4, clk-1, age-1 and mev-1 were analyzed by RT-PCR method for possible C. elegan anti-aging mechanisms of SC-RP. Expression levels of key genes daf-2, gst-4 and sod-3 were up-regulated, while that of daf-16, skn-1, and clk-1 were down-regulated. The results suggest that SC-RP could extend the lifespan and healthspan of C. elegans significantly, and the IIS pathway, SKN-1/Nrf2 pathway and mitochondrial metabolism pathway were primarily considered associated. Thus, SC-RP is a potential component to improve aging and aging-related symptoms as new functional materials.